A new species of Stoliczkia Jerdon, 1870 (Serpentes: Xenodermidae) from Mizoram, India - Lalronunga, Samuel; Lalhmangaiha, K.; Zosangliana, Isaac; Lalhmingliani, Esther; Gower, David J.; Das, Abhijit; Deepak, V. (Zootaxa, 2021)
We describe a new species of Stoliczkia from Mizoram, India. Stoliczkia vanhnuailianai sp. nov. is identified as a member of the genus Stoliczkia by distinct scale arrangements on the posterior of the head, and by scales on the body being separated by scaleless skin, and it differs from the two known congeners in body and head scalation. This is only the third specimen of Stoliczkia collected from India, and the sixth reported specimen for the genus. A revised key to the identification of the species of Stoliczkia is provided.